Development of Face Recognition on Raspberry Pi for Security Enhancement of Smart Home System - Teddy Surya Gunawan; Muhammad Hamdan Hasan Gani; Farah Diyana Abdul Rahman; Mira Kartiwi (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2017)
Nowadays, there is a growing interest in the smart home system using Internet of Things. One of the important aspect in the smart home system is the security capability which can simply lock and unlock the door or the gate. In this paper, we proposed a face recognition security system using Raspberry Pi which can be connected to the smart home system. Eigenface was used the feature extraction, while Principal Component Analysis (PCA) was used as the classifier. The output of face recognition algorithm is then connected to the relay circuit, in which it will lock or unlock the magnetic lock placed at the door. Results showed the effectiveness of our proposed system, in which we obtain around 90% face recognition accuracy. We also proposed a hierarchical image processing approach to reduce the training or testing time while improving the recognition accuracy.